The examiner as a subject of a party to criminal proceedings by the prosecution - Stolitnii, A. (Науковий вісник Ужгородського національного університету. Серія Право, 2024)
It is indicated that the process of modernization of the system of criminal justice bodies is underway in Ukraine, the purpose of which is to improve the system of public administration and improve mechanisms for protecting the rights and freedoms of citizens. In particular, the concept of criminal justice reform of Ukraine, approved by the Decree of the President of Ukraine dated 04/08/2008 No. 311/2008, was implemented in the aspect of updating criminal, criminal procedural and administrative tort legislation. As part of the humanization of criminal legislation, the following steps have been taken: felony crimes have been reclassified as criminal misdemeanors, the procedure for bringing to justice persons who have committed criminal misdemeanors has been simplified, and the work of criminal justice bodies has been optimized in the detection, investigation, and trial of cases. The scientific publication examines topical issues of the place and role of the investigator in criminal proceedings, including through a comparison of the procedural status of the investigator and the investigator. Taking into account the powers of the inquirer, defined by the law that introduces this institute, the burden on the specified subject of criminal proceedings is examined in comparison with the investigator on the example of a specific region, with statistical data on registered, completed and sent to court criminal proceedings. The norms of the current criminal procedural legislation are analyzed, which determine the authority of the inquirer in the process of carrying out a pre-trial investigation of criminal misdemeanors. The legal status of the inquirer as a subject of registration in the Unified Register of Pretrial Investigations is outlined, the imperfection of the introduced norms is noted due to the limitation of the procedural powers of the head of the inquiry in comparison with the head of the investigative unit, and the negative procedural consequences are indicated due to some legislative gaps that require amendments to the current Criminal Code of the procedural code of Ukraine. Based on the results of the research, conclusions and proposals regarding the improvement of national legislation were formulated, and the prospect of further research on this topic was determined.